Bioactivities and Structure–Activity Relationships of Fusidic Acid Derivatives: A Review - Long, Junjun; Ji, Wentao; Zhang, Doudou; Zhu, Yifei; Bi, Yi (Frontiers in Pharmacology, 2021)
Fusidic acid (FA) is a natural tetracyclic triterpene isolated from fungi, which is clinically used for systemic and local staphylococcal infections, including methicillin-resistant Staphylococcus aureus and coagulase-negative staphylococci infections. FA and its derivatives have been shown to possess a wide range of pharmacological activities, including antibacterial, antimalarial, antituberculosis, anticancer, tumor multidrug resistance reversal, anti-inflammation, antifungal, and antiviral activity in vivo and in vitro. The semisynthesis, structural modification and biological activities of fusidic acid derivatives have been extensively studied in recent years. This review summarized the biological activities and structure–activity relationship (SAR) of FA in the last two decades. This summary can prove useful information for drug exploration of fusidic acid derivatives.